2018
DOI: 10.1016/j.jmbbm.2018.06.016
|View full text |Cite
|
Sign up to set email alerts
|

High-velocity micro-particle impact on gelatin and synthetic hydrogel

Abstract: The high-velocity impact response of gelatin and synthetic hydrogel samples is investigated using a laser-based microballistic platform for launching and imaging supersonic micro-particles. The micro-particles are monitored during impact and penetration into the gels using a high-speed multi-frame camera that can record up to 16 images with nanosecond time resolution. The trajectories are compared with a Poncelet model for particle penetration, demonstrating good agreement between experiments and the model for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 39 publications
0
23
0
Order By: Relevance
“…While the dynamics of surface-seal cavities has not been explored in past literature with excessive detail, the fluidic behaviour that is reported is quite similar to our findings. Veysset et al (2018) showed that the impact of a copper microparticle at 435 m s −1 can cause surface dome-over at the surface of a protein hydrogel. Their maximum radius R L /R is found to be R L /R ≈ 5, which is comparable to that obtained from our surface-seal data.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…While the dynamics of surface-seal cavities has not been explored in past literature with excessive detail, the fluidic behaviour that is reported is quite similar to our findings. Veysset et al (2018) showed that the impact of a copper microparticle at 435 m s −1 can cause surface dome-over at the surface of a protein hydrogel. Their maximum radius R L /R is found to be R L /R ≈ 5, which is comparable to that obtained from our surface-seal data.…”
Section: Discussionmentioning
confidence: 99%
“…Veysset et al. (2018) showed that the impact of a copper microparticle at can cause surface dome-over at the surface of a protein hydrogel. Their maximum radius is found to be , which is comparable to that obtained from our surface-seal data.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Microparticles are then deposited on the substrates and spread on the metallic layer using lens cleaning papers and a drop of ethanol. Optionally, an elastomeric layer (30-μm polyurea, not shown in schematics) may be added onto the metallic film before deposition of particles as described, for instance, in Refs [17,25]. In the present case, particles reach higher velocities but are in direct contact with the ablation area.…”
Section: Microparticle Launchermentioning
confidence: 99%
“…The laser-induced particle impact test (LIPIT) is an in-house designed tabletop method for micro-impact experiments. 23 The LIPIT is capable of inducing impacts with strain rates on the order of 10 6 -10 8 s -1 and has been used for testing high strain rate impact responses in gels 24 , segmented elastomers [19][20][21]25 , and other various materials [26][27][28] . Using this platform, Hsieh et al found that intersegmental mixing between the soft and hard phases strongly affected the high strain rate impact response of poly(urethane urea) and polyurea elastomers 21 .…”
mentioning
confidence: 99%